Development of a comfort suit-type soft-wearable robot with flexible artificial muscles for walking assistance - Piao, Jiaoli; Kim, Minseo; Kim, Jeesoo; Kim, Changhwan; Han, Seunghee; Back, Inryeol; Koh, Je sung; Koo, Sumin (Scientific Reports, 2023)
Anchoring components are added to wearable robots to ensure a stable interaction between the suits and the human body and to minimize the displacement of the suits. However, these components can apply pressure to the body and can cause user dissatisfaction, which can decrease willingness to use the suits. Therefore, this study aims to develop a suit-type soft-wearable robot platform for walking assistance by providing comfortable garment pressure to ensure user satisfaction. The first prototype of a wearable robot suit was developed with anchoring components on the shoulders, waist, and thighs based on previous research results. Wear tests were conducted to measure garment pressure depending on posture using pressure sensors, and satisfaction surveys were conducted. The second prototype design was then developed, and performance tests with flexible artificial muscles and a satisfaction survey were conducted. Regarding the first prototype, the participants felt more than normal pressure in the shoulders and relatively less pressure in the thighs and calves. Thus, compared to the first design, the second design ensured a decreased garment pressure and resulted in an improvement of overall user satisfaction. These results can help provide guidance in the development of wearable robots by taking pressure comfort and user satisfaction into consideration.
Keywords: Exoskeleton Device; Humans; Muscles; Robotics; Walking; Wearable Electronic Devices